On n-quasi-(m, C)-isometric operators. Issue 5 (3rd May 2020) - Ould Ahmed Mahmoud, Sid Ahmed; Chō, Muneo; Lee, Ji Eun
ABSTRACT: In this paper, we introduce the class of n -quasi- ( m, C ) -isometric operator on a Hilbert space which is a variation of ( m, C ) -isometric operators Chō M, Ko E, Lee JE. [On ( m, C ) -isometric operators. Complex Anal Oper Theory. 2016;10:1679–1694]. An operator T ∈ B ( H ) is said to be n -quasi- ( m, C ) -isometric if T ∗ n ∑ 0 ≤ k ≤ m ( − 1 ) k m k T ∗ m − k C T m − k C T n = 0 for some positive integers n and m . We study this class of such operators and give some of their basic properties.